Synthesis and Antifungal Activity of 7-Alkyl/aryl-amino-6-fluoro-2-(4-chloro phenyl)carboxamido(1,3)benzothiazole - Sarkar, Sibaji; Shivakumar, B.; Roy, Kalyan (Asian Journal of Chemistry, 2010)
The compounds 7 alkyl /aryl amino-6-fluoro-2-(4-chloro phenyl)carboxamido(1,3)benzothiazoles were synthesized. The newly synthesized compounds shows antifungal activity against Candida albicans and Aspergillus flavus.